Effectiveness of Community Nursing Home Visits Using Interactive Media for Stunting Prevention - Pane, Nikmah Kemalasari; Almadany, Ulfah Hidayah; Batubara, Rini Amalia; Siregar, Miftahul Khoiriyah; Siti Ayu Antira (Journal of Health Empowerment and Interprofessional Practice, 2026)
Background of study: Stunting remains a persistent public health challenge, particularly in community settings where inadequate maternal practices during the first 1,000 days of life contribute to impaired child growth and development. Community nursing interventions that integrate home visits with interactive educational approaches are increasingly recognized as effective strategies to improve caregiving behaviors related to stunting prevention.Aims and scope of paper: This study aimed to examine the effectiveness of community nursing home visits using interactive educational media in improving maternal practices for stunting prevention among caregivers of children aged 0–24 months.Methods: A quasi-experimental study with a one-group pretest–posttest design was conducted in Desa Pintu Langit Jae, Angkola Julu Subdistrict, Padangsidimpuan City, Indonesia. A total of 63 mothers or primary caregivers were selected using purposive sampling. The intervention consisted of home visits conducted by community nurses using interactive educational media, including videos, guided discussions, and practical demonstrations, over a four-week period. Data were collected using structured questionnaires and observation checklists and analyzed using descriptive statistics and paired samples t-test.Result: The results showed a significant improvement in maternal practice scores after the intervention. The mean pretest score was 56.42 (SD = 8.73), increasing to 74.86 (SD = 7.95) in the posttest, with a statistically significant difference (p < 0.001).Conclusion: Community nursing home visits integrated with interactive educational media are effective in improving maternal practices related to stunting prevention and offer a practical, evidence-based approach for strengthening community health programs in resource-limited settings.